The Impact of Audit Quality, Audit Committee and Financial Reporting Quality: Evidence from Malaysia - Hasan, Shahanif; Md Kassim, Aza Azlina; Abdul Hamid, Mohamad Ali (International Journal of Economics and Financial Issues, 2020)
In recent decades, there has been a noticeable increase in the practice of earnings management as a proxy for financial reporting, especially real activities, with effect on the quality of financial statements. The role of the audit committee in mitigating earnings management remains ambiguous because of inconclusive findings. Therefore, this study examines the moderating effect of audit quality and audit committee on financial reporting quality, also known as REM inn Malaysian companies. The results show that corporate governance mechanism such as financial accounting expert, meeting and indicate significant results with real earnings management while, audit committee independence and size, shows an insignificant result on real earnings management. In addition, the results show that audit quality of the audit committee leads to less aggressive earnings management practice in real activities. The findings also show that audit quality and audit committee has a significant role in restricting the real earnings management. Audit quality is found to significantly moderate the relationship between audit committee with financial reporting quality proxy. Overall, this study provides a reference point for the relevant parties such as regulatory bodies, policymakers and standard setters towards improving the quality of earnings and corporate governance practices in ensuring credible accounting information. Keywords: audit committee effectiveness, audit quality, real earnings management, Malaysia JEL Classifications: G3, M42 DOI: https://doi.org/10.32479/ijefi.10136